THECOMPARISON OF TWO DIFFERENT SPORTING EVENTS BASEDONTHETYPICALBEHAVIOROFTHEACTIVE SPECTATORS AND GRANDSTAND VIBRATIONS INDUCED BY THEM - Martin Verner (Acta Polytechnica CTU Proceedings, 2020)
The paper describes especially the typical behavior of two active spectators crowds involved in two substantially different sporting events, namely, ice hockey games and a biathlon world cup competition. In both cases, spectators behavior was observed together with grandstand structure dynamic response to their cheering activities. The experimental results obtained during both events were mutually compared and discussed whether the dynamic loading and its effects on the grandstand structures are similar for the two compared spectators crowds.